2018
DOI: 10.21873/invivo.11223
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor Expression and Angiogenesis – Analysis in the Pituitary Gland and Patterns of Death

Abstract: Abstract. Background The pituitary (hypophysis), a small 0.5-g endocrine gland, is located at the base of the brain, just below the hypothalamus; it is the "master gland" of the neuroendocrine system for it controls the function of other endocrine glands. The pituitary itself is regulated by the hypothalamus that is connected to the pituitary by a thin stalk, the pituitary stalk, which carries a delicate portal venous system. Microscopically, the pituitary is composed of two distinctive parts: the anterior lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…AVM has been described as lesions enlarged through vasculogenesis, involving the formation of new vasculature or angiogenesis to form new blood vessels from the pre-existing vasculature [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. First, the effect of EC proliferation on angiogenesis was evaluated [ 14 , 15 ] and was found to be greater in AVM than in normal tissues. EC proliferation increased in AVM compared to normal tissues under hypoxic conditions, although proliferation generally decreased because of hypoxic damage ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVM has been described as lesions enlarged through vasculogenesis, involving the formation of new vasculature or angiogenesis to form new blood vessels from the pre-existing vasculature [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. First, the effect of EC proliferation on angiogenesis was evaluated [ 14 , 15 ] and was found to be greater in AVM than in normal tissues. EC proliferation increased in AVM compared to normal tissues under hypoxic conditions, although proliferation generally decreased because of hypoxic damage ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, various studies have reported that angiogenesis induced under hypoxia was effectively compared and evaluated in normal and pathophysiological situations using the CD31 expression [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%